TINDAK TUTUR SARKASTIK DI MEDIA SOSIAL (SARCASTIC SPEECH ACTS IN SOCIAL MEDIA) - Wiwin Hardiati (Universitas Lambung Mangkurat, 2018)
AbstractSarcastic Speech Acts in Sosial Media.The research entitled sarcastic speech acts in social media ismotivated by the use of speech acts in social media that contain many sarcastic elements, in this study,there are four themes raised, namely the theme of politics, social themes, cultural themes, and economicthemes, and it based on three types of speech acts, namely directive speech acts, expressive speech acts,and assertive speech acts. This research applied the descriptive method. The sources of data obtained fromsocial media and research data are in forms of words or sentences expressed in social media. Then, thedata were collected through several techniques including classification, analysis, and conclusion. Fromthe results of data analysis, researchers can conclude that the act of sarcastic speech is very dominantin the political theme. Based on the type of speech acts of the four themes,the most frequent one toappear is expressive speech acts. Viewed from expressive speech types, the use of sarcastic speech actsis manifested in a variety of expressive ways of expressing displeasure, criticizing, swearing, mocking,insulting, disparaging, venting, and calling nicknames with discriminatory calls. The sarcastic speech actsthat unconsciously stated can have a negative impact on the psychological conditions of the opponent otthe readers and other people who are along with the utterances.Key words: speech acts, sarcastic, social mediaAbstrakTindak Tutur Sarkastik di Media Sosial. Penelitian ini dilatarbelakangi oleh penggunaan tindak tuturdi media sosial yang banyak mengadung unsur sarkastik, dalam penelian ini ada empat tema yangdiangkat, yaitu tema politik, tema sosial, tema budaya, dan tema ekonomi kemudian berdasarkan daritiga jenis tindak tutur, yaitu tindak tutur direktif, tindak tutur ekspresif, dan tindak tutur asertif. Penelitianini menggunakan metode deskriftif. Sumber data didapat dari media sosial dan data penelitian ini ialahkata-kata atau kalimat yang terdapat di media sosial kemudian dikumpulkan melalui beberapa teknik,diklasifikasi, dianalisis, dan disimpulkan. Berdasarkan hasil analisis data, dapat peneliti simpulkanbahwa tindak tutur sarkastik yang sangat dominan terdapat pada tema politik, sedangkan berdasarkanjenis tindak tutur dari empat tema tersebut yang dominan muncul, yaitu tindak tutur ekspresif. Jikaditinjau dari jenis tuturan ekspresif, penggunaan tindak tutur sarkastik diwujudkan dalam berbagaijenis tindak ekspresif, yaitu mengungkapkan rasa tidak senang, mengkritik, umpatan, ejekan, hinaan,meremehkan, meluapkan, dan memanggil nama panggilan dengan panggilan yang diskriminatif.Sementara itu, jika ditinjau dari fungsi dan maknanya, penggunaan tindak tutur ekspresif mempunyaipotensi yang dapat menimbulkan dampak penggunaan..Kata-kata kunci: tindak tutur, sarkastik, media sosial